Augmented Reality-Based Learning Media to Increase Islamic Financial Literacy - Nurbaiti, Novita; Suyanto, Slamet (Journal of Education Technology, 2022)
Learning Islamic financial literacy from an early age is essential so that it accumulates into adulthood. The application of Islamic financial literacy learning needs to be supported by learning media on the preferences of students' learning styles. The purpose of the research is to analyse augmented reality's effectiveness in increasing Islamic financial literacy for elementary school students. This experimental research tests the effectiveness of augmented reality-based learning media in increasing Islamic financial literacy and analyses students' experiences using the media. The method was quasi-experimental, using 2 groups, namely the experimental group and the control group, with a total sample of 30. Data collection techniques used were test instruments and questionnaires. The data analysis used is the paired sample test and gain value analysis. The results of the paired sample test showed that in the experimental group, there was a significant difference in the pretest and posttest values. Analysis of the gain value in the experimental group was 0.7 (Medium), while in the control class, it was only 0.09 (Low). Students responded well to the user experience of augmented reality media, and the majority (73%) stated that AR was easy to use and understand, had clarity, accommodated user involvement, and had an interest in reusing the media.